Effect of monomer type on acrylic emulsion polymers as pressure-sensitive adhesives - Fady Gamal Fathy Atallah; Ahmed Ismael Hussein; Ihab Foad Abadir (Cairo : Fady Gamal Fathy Atallah, 2014)
This work studies the influence of different monomers types, structures and concentrations on the performance of waterborne acrylic PSAs. A series of PSA samples are prepared and tested under controlled conditions using different base monomer composition ratios of soft monomers, hard monomers and functional monomers. A brief kinetic study, an initial reactor design, and a preliminary feasibility study have also been introduced
Thesis (M.Sc.) - Cairo University - Faculty of Engineering - Department of Chemical Engineering
Issued also as CD
Keywords: Adhesive; Emulsion; Pressure-sensitive